Kilka uwag o obowiązku lojalności radcy prawnego - Wieczorek, Mariusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
Loyalty, construed as honest and reliable behaviour in interpersonal relations, is of particular importance in the case of persons practising professions of public trust. One of the professions mentioned in art. 17 (1) of the Constitution of the Republic of Poland is that of an attorney-at-law. In the present paper, based on the conclusions drawn from the analysis of the provisions of the Act on Attorneys-at-Law and the provisions of the Code of Ethics for Attorneys-at-Law, it has been shown that the duty of loyalty of attorneys-at-law is not limited to customer relations. One can speak about this obligation of an attorney-at-law already at the stage which precedes entering into a legal relationship under which the attorney provides legal assistance to the client. Therefore, it is proposed that, in specific cases, the loyalty of an attorney-at-law may result in a refusal to provide assistance to the client. When this happens, the attorney-at-law should indicate another attorney-at-law who will be able to provide legal assistance to the client in a given case. Furthermore, the duty of loyalty of an attorney-at-law also exists in relations between attorneys-at-law. The paper takes a position which assumes that the mutual loyalty of attorneys-at-law is a necessary condition for practising their profession as a profession of public trust in the constitutional sense of the term.
Keywords: attorney-at-law; loyalty; profession of public trust; ethics of an attorney-at-law